The apothecary diaries. Volume 2 - Hyūga, Natsu; Nanao, Itsuki (Square Enix Manga, 2021)
"When word of her accomplishments falls on the ears of His Imperial Majesty, Maomao finds herself tasked with a direct request from the throne. Turning down the emperor is out of the question for the former apothecary - if she wants to keep her head! But while acquiescing to the emberor is expected of all subjects, Maomao is about to discover that ladies-in-waiting have still more taxing duties to which to attend, as preparations for the garden banquet get underway! Concoting an aphrodisiac might be second nature to Maomao, but smiling prettily for the officials of the court could prove far more difficult..."--Publisher.